Effect of Thiobacillus and Superabsorbent on Essential Oil Components in Thyme Species. Issue 3 (4th May 2019) - Pouramini, Pouneh; Fotokian, Mohammad Hossein; Dehghan, Hossein; Hensel, Goetz
Abstract: Plants of the Lamiacea family have a long tradition in folk medicine and are used as aroma herbs due to their high content of essential oils. The objective of this research was to examine the possibility of improving the quantity and quality of essential oil in thyme through nutrition of the seedlings using Thiobacillus bio-fertilizer and treatment by superabsorbent. For this purpose, seedlings of two thyme species ( Thymus vulgaris and Thymus daenensis ) were sown in pots and exposed to different levels of Thiobacillus and superabsorbent. Results of Gas chromatography/Mass spectrometry (GC/MS) revealed that the main compounds detected for T. vulgaris were thymol (31.5 %), p-cymene (23.4 %), γ-terpinene (13.9 %), linalool (38.3 %) and carvacrol (2.7 %) while the main compounds of T. daenensis were thymol (51.2 %), o -cymene (12.9 %), γ-terpinene (4.5 %), linalool (1.7 %) and borneol (3.1 %). Furthermore, the application of Thiobacillus had a significant effect on α-pinene content (p=0.05). Moreover, the interaction between superabsorbent and Thiobacillus significantly changed the percentage of thymol, borneol, and caryophyllene.